Keanekaragaman Serangga pada Tanaman Semangka (Citrullus lanatus (Thunb.) Mansf.) - Darsono Darsono; Meyla Khasanah (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2018)
The aims of this reseach was to determine the diversity, abundance of insects on watermelon based on ecological function .The method used in this research was survey with a random sampling techniques on watermelon plants. Insect observations conducted in three phases, ie before flowering, during flowering and during fruiting. The results showed the insects were obtained consisting of five orders, ie Orthoptera, Coleoptera, Hemiptera, Hymenoptera and Diptera. The role of each order is fitofag / herbivores are dominated by the family of the order Orthoptera and Coleoptera. Most families from the order Orthoptera, Coleoptera, Hymenoptera and Diptera act as predators. Insects that act as pollinators dominated by the family of the order Hymenoptera and Diptera. The Order Hemiptera act as pests. Insect abundance in watermelon crop was highest in fruiting phases ie 1103 individuals (50.61%).  While the abundance in the phase prior to flowering and during flowering phase successively obtained the total of 132 individuals (10.62%) and 727 individuals (38.77%) respectivelly. Shannon-Wiener Diversity  index (H'), Evenness index (E) of insects in the phase before flowering H '= 1.642, E = 0.3691, in the current phase of flowering H' = 2.231, E = 0, 5474, and the fruiting phase H '= 2.613, E = 0.7575. Based on the ecosystem function the highest diversity was insect pest (H' = 1,56, E 0,6799), following by insect pollinators (H' = 1,44, E 0,8489),   and the lowest was predator (H' = 1,235, E 0,8598), (In watermelon farming, insect community was dominated by pest, escpesially during fruiting phase.